RELATION OF PATTERN ATTITUDE SIT TO THE HAPPENING OF SKOLISOSIS AT CHILD AGE 11-13 YEAR IN SDN PABELAN KARTASURA - Rahkmad Rosadi (Jurnal Keperawatan, 2011)
Scoliosis represent definition from disparity of backbone where happened backbone formation deviation if seen and behind existence of backbone curve up at lateral (beside) followed with rotation. Target of this research is to know attitude pattern relation sit to the happening of scoliosis at age child11-13 year in SDN Pabelan Kartasura. This research use type research of analytic observational designed by cross sectional study, that is free variable and tied to be measured concurrently. Research subject is elementary schoolboy counted 63 childs with total sampling technique. After analyzed to usechi-square tests show result, founded by 31 subjects was scoliosis, scoliosis pursuant to cause the happening of scoliosis is attitude hunch up 21 child, straightening 4 child, and oblique 6 child. Proved statistically attitude pattern relation sit with the happening of scoliosis at age child 11-13 year in SDNPabelan Kartasura use chi-square tests, p-value = 0,000 < 0,05 that mean Ha is accepted.